Metamemory functioning and memory strategies used among medical students - Kinjari Kancharla; Sagayaraj Kanagaraj; C N Ram Gopal (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Metamemory can be described as an intentional endeavor to guide or control one's memory processes. In other words, awareness and knowledge of one's own memory process and strategies for using the memories effectively. Planning, allocating cognitive resources, selecting strategies, assessing understanding, and evaluating performance all rely heavily on metamemorial information. For efficient learning, good memory abilities are necessary. This study aimed to understand metamemory functioning and to see if there were any gender differences in metamemory functioning among medical students. MATERIALS AND METHODS: This cross-sectional study was conducted by collecting data from 350 medical students using the Memory Functioning Questionnaire in 2021. The sample group was selected from medical colleges in South India such as Kerala, Karnataka, Tamil Nadu, Telangana, and Andhra Pradesh using a purposive sampling technique. This questionnaire focused on the seriousness of forgetting, the rate at which people recalled things over time, and frequency of use of mnemonics and techniques that assist memory. Descriptive statistics, independent sample t-test, correlation, and regression were used for analysis. RESULTS: There was a significant difference based on gender among medical students in general memory functioning and frequency of forgetting (P < 0.001). Similarly, it was also found that gender was a major predictor of general memory functioning and frequency of forgetting among medical students (P < 0.001). CONCLUSION: Most medical students believe they have a minor memory issue. Even if the majority of medical students forget information, the vast majority of them believe they have an exceptional memory. Gender acts as a significant predictor of general memory performance and forgetfulness.